Legal Aid Program for Mining Cases between PT Tambang Mas Sangihe and the Sangihe Community: Program Bantuan Hukum atas Kasus Pertambangan antara PT Tambang Mas Sangihe dengan Masyarakat Sangihe - Arisa Risma Rizalda; Rosa De Lima Gita Sekarjati; Tarissa Putri Hanifah; Azzahra Ditha Purnama; Dena Cahya Setia Putri (The Indonesian Journal of International Clinical Legal Education, 2022)
The abundant gold content makes the Sangihe Islands Regency the prima donna of entrepreneurs who are contested to open additional land in the Regency. One of the mining companies interested in opening mining areas is a Canadian company, PT Tambang Mas Sangihe (TMS). The company is a Contract of Work holder with an area of ​​57% of the total area of ​​the Sangihe Islands Regency or about 42,000 hectares. The existence of mining not only brings economic benefits, but also has negative impacts that must be considered. The most affected parties are the community, especially local residents. Damage to the environment, natural disasters, social and other problems become the shadow of people's lives. Utilization of natural resources needs to be carried out in a balanced manner so that it does not only achieve economic needs but also does not sacrifice nature and the social community, especially the local residents of the Sangihe Islands Regency.